Evaluation of urban public transport sustainability in China based on the Driving Force-Pressure-State-Impact-Response (DPSIR) framework——a case study of 36 major cities - Hou, Xiaoran (2023)
With urbanization and motorization, the sustainable development of urban transport has drawn extensive attention worldwide. As one of the key components of the transport system, urban public transport is the breakthrough. This study focused on the characteristics of public transport, analyzed the causal and restrictive relationships between anthropogenic activities and urban public transport sustainability based on the Driving Force-Pressure-State-Impact-Response (DPSIR) framework, and decomposed the interaction to establish an evaluation index system. An improved set pair analysis-variable fuzzy set model (ISPA-VFSM) was constructed to evaluate urban public transport sustainability in China's 36 major cities in 2020 and analyze the critical influence factors and restriction modes according to the contribution degree and obstacle degree. The results show that: (1) The sustainable development of urban public transport is a systematic process, and public transport sustainability in 36 major cities shows the spatial distribution characteristics of “high in the southeast and low in the west;” Most megacities are at the forefront, benefiting from outstanding state and response levels, with Shenzhen ranking first; while the megapolises generally display moderate sustainability. Cities in Northeast and Northwest China present lower levels of sustainability. (2) Public transport sustainability in China is deficient, exhibiting a certain gap from the target. The levels of the driving force, pressure, state, impact, and response of public transport sustainability in 36 major cities are unbalanced; (3) The restriction mode of urban public transport sustainability in 36 major cities can be roughly divided into three categories: pressure-impact restriction mode, driving force-impact restriction mode, and state-response restriction mode; (4) State and response play a crucial role in achieving public transport sustainability. Public transport infrastructure, electrification substitution, and efficiency of public transport operations are the primary contributing factors to public transport sustainability. This study enriches the indicators and methods for sustainability evaluation and provides a reference for urban public transport sustainable development.